Conjugated polyelectrolytes : fundamentals and applications - Liu, Bin.; Bazan, G. (Weinheim : Wiley-VCH, 2013)
"This is the first monograph to specifically focus on fundamentals and applications of polyelectrolytes, a class of molecules that gained substantial interest due to their unique combination of properties. Combining both features of organic semiconductors and polyelectrolytes, they offer a broad field for fundamental research as well as applications to analytical chemistry, optical imaging, and opto-electronic devices. The initial chapters introduce readers to the synthesis, optical and electrical properties of various conjugated polyelectrolytes. This is followed by chapters on the applications of these materials in optical sensing and imaging with emphasis on biological systems, while the final section addresses the emerging applications of conjugated polyelectrolytes in optoelectronic devices, concluding with an in-depth discussion of structure-property relationship. The editors and contributors are all pioneers and experts in this expanding field. This monograph is not only for chemists, materials scientists, and physicists, but also a unique source of knowledge for readers with scientific background interested in polyelectrolytes."--
Design and Synthesis of Conjugated Polyelectrolytes / Kan-Yi Pu, Guan Wang, Bin Liu -- All-Conjugated-Diblock Copolymers Containing Conjugated Polyelectrolyte Blocks / Ullrich Scherf, Rachel C Evans, Andrea Gutacker, Guillermo C Bazan -- Ionically Functionalized Polyacetylenes / Stephen G Robinson, Mark C Lonergan -- Aggregation Properties of Conjugated Polyelectrolytes / Hugh D Burrows, Matti Knaapila, Sofia M Fonseca, Telma Costa -- Sensing via Quenching of Conjugated Polyelectrolyte Fluorescence / Danlu Wu, Jie Yang, Fude Feng, Kirk S Schanze -- Sensing Applications via Energy Transfer from Conjugated Polyelectrolytes / Fengting Lv, Shu Wang, Guillermo C Bazan -- Sensing via Conformational Changes of Conjugated Polythiophenes / Even J Lemieux, Mario Leclerc -- Conjugated Polyelectrolyte-Based Biocide Applications / Thomas S Corbitt, Eunkyung Ji, Ying Wang, Anand Parthasarathy, Kristin N Wilde, Eric H Hill, Dimitri Dascier, Heather E Canavan, Eva Y Chi, Kirk S Schanze, David G Whitten -- Conjugated Polyelectrolyte-Based Imaging and Monitoring of Protein Aggregation / K Peter R Nilsson, Per Hammarström -- Charge Injection Mechanism in PLEDs and Charge Transport in Conjugated Polyelectrolytes / Peter Zalar, Thuc-Quyen Nguyen -- Organic Optoelectronic Devices Containing Water/Alcohol-Soluble Conjugated Polymers and Conjugated Polyelectrolytes / Sujun Hu, Chengmei Zhong, Hongbin Wu, Yong Cao -- Optical Processes in Conjugated Polyelectrolytes Dependence on Chain Conformation and Film Morphology / Giuseppina Pace, Richard Friend.
Includes bibliographical references and index.
Print version record.
Keywords: Polyelectrolytes; Conjugated polymers; SCIENCE -- Chemistry -- Physical & Theoretical; Conjugated polymers; Polyelectrolytes; Electronic books; Electronic books